2007
DOI: 10.1183/09031936.00078107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum markers for allergic bronchopulmonary aspergillosis in cystic fibrosis

Abstract: The diagnosis of allergic bronchopulmonary aspergillosis (ABPA) in cystic fibrosis (CF) is a challenge. Thymus-and activation-regulated chemokine (TARC) has recently been reported to play a role in ABPA. The aim of this study was to compare the diagnostic value of TARC with that of known serological markers for diagnosis of ABPA in CF patients.The present study longitudinally followed 48 CF patients, of whom 12 had a diagnosis of ABPA according to Nelson's criteria, for 1-8 yrs with repeated measurements of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 38 publications
1
48
1
2
Order By: Relevance
“…Kraemer et al (13) have shown that allergen-specific IgE against these two recombinants could be detected almost exclusively in the sera of patients with ABPA. rAspf4 sensitivity is usually higher than that of rAspf6 (6, 11), but not for Latzin et al (15). In comparison, the sensitivities obtained in our work were 92.3% for rAspf4 and 53.8% for rAspf6.…”
Section: Discussionmentioning
confidence: 42%
“…Kraemer et al (13) have shown that allergen-specific IgE against these two recombinants could be detected almost exclusively in the sera of patients with ABPA. rAspf4 sensitivity is usually higher than that of rAspf6 (6, 11), but not for Latzin et al (15). In comparison, the sensitivities obtained in our work were 92.3% for rAspf4 and 53.8% for rAspf6.…”
Section: Discussionmentioning
confidence: 42%
“…56 Some immunological manifestations include recurrent episodes of eosinophilic airways inflammation, peripheral blood eosinophilia, increased serum concentrations of IL-2 receptor, high total serum IgE levels, and increased circulating specific IgE and IgG against A. fumigatus antigen. 56,72,73 The pathophysiology of ABPA still remains largely speculative, nonetheless several predisposing factors have been proposed for ABPA development.…”
Section: Abpamentioning
confidence: 99%
“…The addition of other tests, such as antigen detection tests for galactomannan, which is released during hyphal growth, can help confirm active organisms, although may be falsely positive because of antibiotic therapy. Other potential biomarkers such as basophil CD203c and thymus activation and regulated cytokine may also have roles in evaluating Aspergillus disease in CF [15].…”
Section: Methods Of Detection Of Aspergillusmentioning
confidence: 99%